Streams and plasma parameters experimental studies in He-CO gas mixtures - Radam, Hamid K. (Iraqi Journal of Physics, 2010)
DC glow discharges were generated between a thin cylindrical anode and a flat cathode, streamers are thought to propagate by photo-ionization; the parameters of photo-ionization depend on the He: CO ratio. Therefore we study streamers in He ( 90%, 80% and 70% ) with (10%, 20% and 30%) CO respectively. The streamer diameter is essentially the change by increase for similar voltage and pressure in all He-CO mixtures.